Vitamin K antagonists - Steffel, J.; Luscher, T. F. (Hämostaseologie, 2012)
For the last decades, anticoagulation for stroke prevention in atrial fibrillation (AF) as well as for the prophylaxis and long-term treatment of venous thromboembolism has been entirely based on vitamin K antagonists (VKA). Although very effective under optimal conditions, long-term treatment with these drugs is flawed by the fact that the time in the therapeutic range frequently is suboptimal due to biological factors, drug interactions and compliance.The direct thrombin inhibitor dabigatran, as well as the direct FXa inhibitors rivaroxaban and apixaban provide more consistent anticoagulation and have proven their efficacy and safety against VKAs in several large scale randomized clinical trials for stroke prevention in atrial fibrillation as well as for the treatment and prevention of venous thromboembolism. In view of these convincing data and other advantages such as the lack of mandatory monitoring and only few drug interactions,VKAs will most likely be replaced in a majority of patients for these indications. Based on the most recent trial evidence, the current review discusses the role of VKA treatmentand that of the novel anticoagulants.
Keywords: Apixaban; atrial fibrillation; dabigatran; ovel oral anticoagulants; rivaroxaban; RE-LY; AVERROES; ARISTOTLE; ROCKET AF